Perspectives on New Testament textual criticism : collected essays, 1962-2004 - Epp, Eldon Jay. (Novum Testamentum, Supplements, 2005)
This collection of frequently cited articles and chapters published from 1962 to 2004 provides perspective on the history and development of New Testament textual criticism, with descriptions and critique of the major text-critical theories and methods. Specific manuscripts and text-types, such as the Codex Bezae and the D-text are discussed, as well as issues such as anti-Judaic tendencies, the ascension narratives, and the relationship of text and canon. Many of the essays from the last fifteen years emphasize the earliest period and papyrus manuscripts, particularly those found at Oxyrhynchus, and assess their socio-cultural and intellectual contexts, while articles from the last five years advocate or engage the more controversial aspects of current New Testament textual criticism, especially the issue of 'original text'.